Willingness to pay for eco-certified hotels in the Mexican context. Comparative study through hedonic prices - Rodríguez-Rudi, Giselle (2023)
Environmental strategies in tourism reduce the negative impact of this sector while seeking to achieve positive effects on its competitiveness and differentiation. However, there is still a research gap in the academic literature on the connection between eco-certifications and the prices that clients are willing to pay for this type of service. This paper analyzes guests’ willingness to pay for rooms in environmentally friendly hotels in Mexico. The study focuses on three of the states with the largest number of hotel establishments in the country: Quintana Roo, Veracruz, and Jalisco. The differences among the states regarding the willingness of the guests to pay for hotels with eco-certification were evaluated by taking into account the category of the establishment. Hedonic price models were used to evaluate the effect of both eco-certification and different hotel attributes on the price of a room. Information regarding prices was obtained from the Trivago database, and the equations were estimated by taking into account data panel techniques. The results show a significant effect on the willingness to pay for hotels with eco-certifications, with differences among states and categories. The limitation of this research is the time of data collection and the place of application.